Toxic Cyanobacteria in Water A Guide to Their Public Health Consequences, Monitoring and Management - Chorus, Ingrid; Welker, Martin (Taylor & Francis, 2021)
"Cyanobacterial toxins are among the hazardous substances most widely found in water. They occur naturally, but concentrations hazardous to human health are usually due to human activity. Therefore, to protect human health, managing lakes, reservoirs and rivers to prevent cyanobacterial blooms is critical. This second edition of Toxic Cyanobacteria in Water presents the current state of knowledge on the occurrence of cyanobacteria and cyanotoxins as well as their impacts on health through water-related exposure pathways, chiefly drinking-water and recreational activity. It provides scientific and technical background information to support hazard identification, assessment and prioritisation of the risks posed by cyanotoxins, and it outlines approaches for their management at each step of the water-use system. It sets out key practical considerations for developing management strategies, implementing efficient measures and designing monitoring programmes. This enables stakeholders to evaluate whether there is a health risk from toxic cyanobacteria and to mitigate it with appropriate measures. This book is intended for those working on toxic cyanobacteria with a specific focus on public health protection. It intends to empower professionals from different disciplines to communicate and cooperate for sustainable management of toxic cyanobacteria, including public health workers, ecologists, academics, and catchment and waterbody managers. Ingrid Chorus headed the department for Drinking-Water and Swimming-Pool Hygiene at the German Environment Agency. Martin Welker is a limnologist and microbiologist, currently with bioMérieux in Lyon, France."